Restorative Justice Crime Of Narcotics In The Elderly With Narcotic Evidence - Bayu Sasongko; Megawati Barthos; Suparno Suparno (CV. Publikasi Indonesia, 2023)
The fact that there is numerous abuse of narcotics and dangerous drugs in Indonesia today is inseparable from the many modes and justifications used by these abusers in carrying out their actions. The exploration is remembered for the regularizing juridical assessment, the strategy involved by the creator as the peculiarities concentrate on that happens connected with the utilization of helpful equity in drug cases has been performed at the examination site. The results are that the Crook Code Bill has thought about the age of the more established in the criminal system, by setting the age north of 75 years for guilty parties of criminal goes about very far they are not open to confinement. In the conversation of Article 72 of the Lawbreaker Code Bill, this age limit was deferred, between the time of